ESP Lecturers’ Individual – Initiated Professional Development: Perceptions and Practices - Sri Diana (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Research on the teacher professional development (TPD) field has rapidly developed in the area of English Language Teaching. Those studies have confirmed that the impact of professional development activities do have positive impact on teachers’ professional practices. However, most of studies reported in the research literature on teacher professional development have been conducted in the area of English language teaching and learning of General English but very little research has been conducted on teacher professional development in the area of English for Specific Purpose (ESP). Therefore this future study aims to explore individual-initiated professional development of ESP lecturers in improving their professional teaching practices in higher education level. This research will employ mixed methods research for data collection. Mixed method study focuses on collecting, analyzing and mixing both data from quantitative and qualitative in a single or series of research.